Application of carbon fibers to flexible, miniaturized wire/fiber-shaped energy conversion and storage devices. Issue 6 (17th January 2017) - Cai, Xin; Zhang, Chaoqun; Zhang, Shengsen; Fang, Yueping; Zou, Dechun
Abstract : An overview of recent progress in wire/fiber-shaped flexible power devices made from micro-carbon fibers is given. Abstract : Carbon fibers (CFs) and CF-reinforced composites have been widely used as high performance structural materials in various military and civilian fields for decades. Owing to the rapid advances and boom in flexible/wearable electronics, CF materials endowed with excellent material properties have received great attention for building lightweight, cost-efficient and miniaturized flexible/wearable energy devices. Herein, a detailed overview of recent progress in wire/fiber-shaped flexible power devices made from micro-CFs is given for the first time. With an emphasis on electrode materials and architecture designs, CF-based wire/fiber energy devices including fiber nanogenerators, wire/fiber solar cells, wire-type batteries, fiber supercapacitors and integrated/hybrid fiber devices are discussed. Aiming to motivate more exciting applications, research directions and perspectives, efficient flexible wire-type CF energy devices are proposed.